Vaccination with Human Induced Pluripotent Stem Cells Creates an Antigen-Specific Immune Response Against HIV-1 gp160 - Yoshizaki, Shinji; Nishi, Mayuko; Kondo, Asami; Kojima, Yoshitsugu; Yamamoto, Naoki; Ryo, Akihide (Frontiers in Microbiology, 2011)
Induced pluripotent stem cells (iPSCs) are artificially derived from somatic cells that have been transduced with defined reprogramming factors. A previous report has indicated the possibility of using iPSCs as an immune stimulator to generate antigen-specific immunity. In our current study, we have investigated whether human iPSCs (hiPSCs) have the ability to enhance specific immune response against a human immunodeficiency virus type 1 (HIV-1) antigen in a xenogenic mouse model. Our results show that BALB/c mice immunized with hiPSCs transduced with an adenoviral vector encoding HIV-1 gp160 exhibited prominent antigen-specific cellular immune responses. We further found that pre-treatment of hiPSCs with ionizing radiation promotes the secretion of pro-inflammatory cytokines such as interleukin-1 alpha (IL-1α), IL-12 and IL-18. These cytokines might promote the activation of antigen-presenting cells and the effective induction of cellular immunity. Our present findings thus demonstrate that a hiPSCs-based vaccine has the potential to generate cellular immunity against viral antigens such as HIV-1 gp160 in a xenogenic condition.